2007 International Conference on Collaborative Computing: Networking, Applications and Worksharing (CollaborateCom 2007) 2007
DOI: 10.1109/colcom.2007.4553835
|View full text |Cite
|
Sign up to set email alerts
|

Using context to assist the adaptation of protected multimedia content in virtual collaboration applications

Abstract: This paper proposes a framework for a virtual classroom application based on a Virtual Collaboration System (VCS), which is being developed under the VISNET II Network of Excellence (NoE) 1 , and discusses adaptation technologies that enable seamless access to classroom sessions while intellectual property and digital rights are managed. The proposed virtual classroom framework enables academic institutions to conduct their collaborative lecture series, to which registered students will be able to attend remot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Enterprises have also found benefit in the web allowing communication between workers to improve their collaboration; however, as established by Zhu [14] adaptability is a key element in a collaboration environment. As seen in [1] an adaptive collaboration framework for a virtual classroom application, adaptive collaboration greatly improves learning compared to a scenario where adaptation is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Enterprises have also found benefit in the web allowing communication between workers to improve their collaboration; however, as established by Zhu [14] adaptability is a key element in a collaboration environment. As seen in [1] an adaptive collaboration framework for a virtual classroom application, adaptive collaboration greatly improves learning compared to a scenario where adaptation is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…During the following discussions, we first describe the Virtual Collaboration application scenario, in which our work is applied. Then, we propose potential extensions to the available MPEG-21 DIA UEDs, as our previous research showed that the existing UEDs do not present adequate descriptions for Virtual Collaboration application scenarios [2].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these profiles consists of sets of the corresponding elements of MPEG-21 DIA UED to assure a full compliance with the standard. A detailed description of these profiles can be found in [5].…”
Section: A Profilingmentioning
confidence: 99%
“…They are similar to the descriptions that humans build, and yet can be used by machines. Decision taking operations that use an ontological framework to describe the context and relationships have thus higher chances to deliver decisions closer to the human way of reasoning, and hence to the users' expectations [5]. They are triggered by low-level context generated by sensors, notifying changes in the consumption environment.…”
Section: Using Ontologies Within the Adaptation Decisionmentioning
confidence: 99%
See 1 more Smart Citation